The emergence of diverse organic consumers: Who are they and how do they shape demand? - Thomas Bøker Lund; Laura Mørch Andersen; Katherine O'Doherty Jensen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
This study uses qualitative and quantitative data as well as household panel data regarding actual purchases of organic food in order to examine organic consumer profiles and recent developments of organic demand in Denmark. Six different segments of Danish households are identified, of which three are either indifferent or negative towards organic foods. Three distinct positively minded segments are also identified. These positively minded segments hold a very high share of all organic food sales on the Danish market and are also driving demand forward. This market can thus be said to be highly polarised. It can also be said to have matured insofar as positively oriented segments that differ in their food involvement, shopping behaviour and levels of ethical concern have appeared, while marketing and distribution strategies have co-developed with these trends. We discuss the current relevance of segmenting organic consumers in mature markets with a view to improving strategies of production, distribution and marketing of organic foods.
Keywords: 330